Trade and unemployment: what do the data say? - Gabriel Felbermayr; Julien Prat; Hans-Jörg Schmerer (Institute for the Study of Labor (IZA), 2009)
This paper documents a robust empirical regularity: in the long-run, higher trade openness is causally associated to a lower structural rate of unemployment. We establish this fact using: (i) panel data from 20 OECD countries, (ii) cross-sectional data on a larger set of countries. The time structure of the panel data allows us to deal with endogeneity concerns, whereas cross-sectional data make it possible to instrument openness by its geographical component. In both setups, we carefully purge the data from business cycle effects, include a host of institutional and geographical variables, and control for within-country trade. Our main finding is robust to various definitions of unemployment rates and openness measures. The preferred specification suggests that a 10 percent increase in total trade openness reduces unemployment by about one percentage point. Moreover, we show that openness affects unemployment mainly through its effect on TFP and that labor market institutions do not appear to condition the effect of openness.
urn:nbn:de:101:1-2009061282
Keywords: F16; E24; J6; 330; International trade; real openness; unemployment; GMM models; IV estimation; Außenwirtschaft; Politik der offenen Tür; Strukturelle Arbeitslosigkeit; Panel; OECD-Staaten